PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA APARATUR SIPIL NEGARA PADA SEKRETARIAT DPRD KAB. INDRAGIRI HILIR - Nina Winarni; Ahmad Rifa'i; Asniati Bindas (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2026)
This study aims to determine the effect of emotional intelligence on the performance of State Civil Apparatus (ASN) at the Secretariat of the Regional House of Representatives (DPRD) of Indragiri Hilir Regency. This research uses a quantitative approach with a survey method. The population in this study consisted of all ASN at the DPRD Secretariat of Indragiri Hilir Regency totaling 60 employees, therefore the sampling technique used was the census method. Data collection was carried out through the distribution of questionnaires using a Likert scale. The data analysis techniques used include validity testing, reliability testing, classical assumption testing, simple linear regression analysis, t-test, and coefficient of determination. The results showed that the emotional intelligence of ASN was in the good category with an average score of 4.12, while ASN performance was also in the good category with an average score of 4.18. The regression analysis results indicated that emotional intelligence had a positive and significant effect on ASN performance at the DPRD Secretariat of Indragiri Hilir Regency. The coefficient of determination test results showed that emotional intelligence contributed 53.8% to ASN performance, while the remaining 46.2% was influenced by other variables not examined in this study.